Effects of Purgative Manna on the Serum Bilirubin Level of Newborns: A Systematic Review and Meta-analysis - Moloud Fakhri; Mohammad Azadbakht; Roya Farhadi (Mazandaran University of Medical Sciences, 2024)
Background: The rate of neonatal jaundice is increasing. Due to the complications associated with phototherapy, researchers have consistently sought alternative methods, including herbal remedies. Objectives: In this study, we conduct a systematic review and meta-analysis to investigate the impact of Purgative manna consumption on the serum bilirubin levels of neonates. Methods: In this systematic review and meta-analysis, we conducted an online search on various databases, including Barakat Gostar, scientific information database (SID), Magiran, IranDoc, PubMed, Scopus, Web of Science, Cochrane and the Google Scholar search engine, without time restrictions, up to July 20, 2023. Data analysis was performed using the STATA software, version 14. Meanwhile, the significance level was considered P<0.05. Results: We examined 12 clinical trial articles, involving a total of 1557 neonates. Before the intervention, there was no statistically significant difference in the bilirubin levels of neonates between the two groups (standardized mean difference [SMD]=-0.02; 95% confidence interval [CI], -0.12%, 0.09%; P=0.473). After Cotoneaster consumption, the serum bilirubin levels of the intervention group decreased (SMD=-3.50; 95% CI, -5.76%, -1.24%; P=0.000). Following phototherapy, the bilirubin levels of the control group also decreased (SMD=-2.14; 95% CI, -4.01%, -0.27%; P=0.000). After the intervention, at 12 h (SMD=-0.45; 95% CI, -0.80%, -0.10%; P=0.000), 24 h (SMD=-0.63; 95% CI, -1%, -0.26%; P=0.000), 36 h (SMD=-0.95; 95% CI, -1.69%, -0.20%; P=0.000), 48 h (SMD=-0.62; 95% CI, -0.92%, -0.31%; P=0.000), and 72 h (SMD=-0.84; 95% CI, -1.40%, -0.29%; P=0.000) post-intervention, the bilirubin levels of neonates in the Cotoneaster group were lower compared to the control group. Conclusions: Cotoneaster consumption is more effective than phototherapy alone in reducing the bilirubin levels of neonates.